2009
DOI: 10.1111/j.1447-0349.2009.00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐esteem in patients treated for anorexia nervosa

Abstract: Anorexia nervosa (AN) mainly affects girls or women between 13 and 45 years of age. According to previous studies, one of the reasons for the desire to be thin is low self-esteem. The purpose of the study was to examine the self-esteem of 38 female patients with AN between 16 and 25 years of age, before and after 3 months of treatment at a specialist ward for eating disorders in Göteborg, Sweden. A quantitative pre- and post-assessment based on two self-rating questionnaires, the Rosenberg Self-Esteem Scale (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 24 publications
5
21
0
2
Order By: Relevance
“…These results could be an argument for the transdiagnostic theory of eating disorder [31] in which a division within ED subdiagnoses are not so relevant. The relation with body attitude and self-esteem and depression is in agreement with the literature [32][33][34][35][36].…”
Section: Discussionsupporting
confidence: 80%
“…These results could be an argument for the transdiagnostic theory of eating disorder [31] in which a division within ED subdiagnoses are not so relevant. The relation with body attitude and self-esteem and depression is in agreement with the literature [32][33][34][35][36].…”
Section: Discussionsupporting
confidence: 80%
“…Karpowicz, Skärsäter and Nevonen [24] suggest that food restriction and purging behaviors are secondary to the primacy of emotional factors in the etiology of ED, especially self-esteem. These authors point out that low self-esteem causes feelings of loneliness, depression and anxiety, i.e., the experience of comfort with oneself and one´s body can be regarded as a central element of the individual´s welfare.…”
Section: Recurrent Thoughts About Foodmentioning
confidence: 99%
“…Low self-esteem plays an important role in understanding psychological issues, psychopathology, and maladjustment through loneliness, depression, and anxiety (Karpowicz et al, 2009). Paterson et al (2007) suggested that by considering a model of self-esteem that includes self-belief, appraisals and efficacy, it could be postulated that low self-esteem in relation to disordered eating facilitates the use of maladaptive coping strategies or hindering implementation of effective techniques.…”
Section: Self-esteemmentioning
confidence: 99%
“…Furthermore, people with low self-esteem "struggle with far more self-criticism than high self-esteem people, setting up a vicious circle of a dip in mood triggering self-criticism that triggers a further dip in mood" (Gilbert & Procter, 2006, p. 354). Karpowicz, Skarsater, and Nevonen (2009) asserted that the concept of selfesteem has two meanings: how a person regards her capacity to do things, and the value she ascribes to herself. People with low self-esteem see themselves as worse than others, are dissatisfied with themselves, self-loathing, and lack respect for their own persona (Karpowicz et al, 2009).…”
Section: Self-esteemmentioning
confidence: 99%
See 1 more Smart Citation